Führung von Hybrid-Teams - Gedanken zum Umgang mit Führung in Zeiten der Corona-Pandemie - Susanna Minder (IUBH Internationale Hochschule, 2020)
– In times of the Corona pandemic, many things are different - including the demands on managers and leaders. The traditionally defined work team almost no longer exists, as distance rules, hygiene measures and risk assessments make it difficult to work in communal areas. To address these issues, many organizations have asked their employees to do more of their work in their home offices, where and whenever possible. This has resulted in a new work structure in which several home office employees work together with a small number of staff in presence. This classic structure of a hybrid team is thus increasingly replacing traditional or purely virtual teams in work organization. These new hybrid structures pose new challenges for managers and leaders. This article deals with thoughts on these changes in everyday work. A distinction is made between a working group and a work team in order to derive the differences in work behaviour or structure between hybrid and traditional or virtual teams. Requirements that arise from this for managers and leaders as well as first considerations are shown. The article thus forms the basis for further research questions that deal with the topic of leadership and the tasks of leading hybrid teams.
Keywords: M54; 330; Covid-19; Corona-Pandemie; Personalmanagement; Personalführung; Führungsherausforderung; Führungsstile; Führung in virtuellen Teams; Führung in Hybrid-Teams